Răspuns :
546 + 127 - 96 : 3 +73 x 2 - (62 : a +24: 2) -5 x 11= 689
673 - 32+ 146- (62 : a +12) - 55= 689
787 - ( 62 : a + 12) -55 = 689
732 -(62 : a +12 ) = 689
732 - 689 =62 : a +12
43 = 62 : a +12
43-12= 62 : a
62:a = 31
a = 62 : 31
a =2
673 - 32+ 146- (62 : a +12) - 55= 689
787 - ( 62 : a + 12) -55 = 689
732 -(62 : a +12 ) = 689
732 - 689 =62 : a +12
43 = 62 : a +12
43-12= 62 : a
62:a = 31
a = 62 : 31
a =2
[tex]673-32+146-(62:a+12)-55=689 \\ 787-(62:a+12)=689+55 \\ -(62:a+12)=744-787 \\ -(62:a+12)=-43(-1) \\ 62:a=43-12 \\ a=63:31 \\ a=2[/tex]